Peningkatan Manajemen Usaha Ekowisata Mangrove Pada Pokdarwis Polaria Tanjungpagar di Desa Mendalok - Yeni Hurriyani; Arfena Deah Lestari (Jurnal Pemberdayaan Masyarakat, 2020)
Mendalok Village is located in the northern coastal region of West Kalimantan which has a potential of 10 hectares of mangrove forest. The problem experienced by partners is the lack of knowledge and skills in developing a mangrove ecotourism business. The financial management is still very simple and the potential of existing mangrove forest products is only sold in fresh form at low prices. The method of implementing this program includes training and guidance on business financial book keeping management, how to make various processed products of mangrove forest products, as well as promotional strategies for tourism business and product marketing from partners. After the training and mentoring on ecotourism business management, the level of understanding of the participants were increased. Participants are able to do neat book keeping either through recording in an accounting book or an excel program. Participants were also able to process mangrove fruit and clam meat, become processed foods and drinks, and make souvenirs from shells and snails. Participants were also able to process mangrove fruit become processed foods and drinks. The partners also get insight in the development of ecotourism business in the future so that it becomes more developed and advanced.